The Use of Emergency Curriculum Digital Books for the Subject of Aqidah Akhlak on Students' Understanding at MTs Al-Ghozali Jatibarang - Sunanto (Quality : Journal Of Education, Arabic And Islamic Studies, 2025)
The digital book of emergency curriculum for the subject of faith and ethics can be interpreted as sheets in the form of files used by students as a guideline in the learning process, as well as several assignments in the form of questions or activities or practices. The digital book of emergency curriculum for the subject of faith and ethics is one of the learning media used in teaching and learning activities in class IX MTs Al Ghazali Kebulen, Jatibarang District, Indramayu Regency. It is hoped that the use of the digital book of emergency curriculum for the subject of faith and ethics can improve the understanding of class IX students of MTs Al Ghazali Kebulen, Jatibarang District, Indramayu Regency. The purpose of this study was to determine the understanding obtained by students of the subject of faith and ethics and the effect of using the digital book of emergency curriculum for the subject of faith and ethics on students' understanding. This research method uses an analysis study with a qualitative approach and data collection techniques through daily tests and questionnaires. Based on the research results obtained, it can be concluded that the use of digital emergency curriculum books for the subject of aqidah and akhlak is classified as good, as evidenced by the results of the distributed questionnaire showing that many respondents answered "Yes" to several questions and the test scores reached above the minimum. digital kurikulum darurat mata pelajaran akidah akhlak dapat diartikan sebuah lembaran-lembaran dalam bentuk file yang digunakan oleh peserta didik sebagai pedoman dalam proses pembelajaran, serta beberapa tugas yang berupa soal-soal maupun kegiatan atau praktik. Buku digital kurikulum darurat mata pelajaran akidah akhlak merupakan salah satu media pembelajaran yang digunakan dalam kegiatan belajar mengajar di kelas IX Mts Al Ghazali Kebulen Kecamatan Jatibarang Kabupaten Indramayu. Diharapkan penggunaan buku digital kurikulum darurat mata pelajaran akidah akhlak dapat meningkatkan pemahaman peserta didik kelas IX Mts Al Ghazali Kebulen Kecamatan Jatibarang Kabupaten Indramayu. Tujuan dari penelitian ini adalah untuk mengetahui pemahaman yang diperoleh peserta didik terhadap mata pelajaran akidah akhlak dan pengaruh penggunaan buku digital kurikulum darurat mata pelajaran akidah akhlak terhadap pemahaman peserta didik. Metode penelitian ini menggunakan studi analisis dengan pendekatan kualitatif serta teknik pengumpulan datanya melalui ulangan harian dan penyebaran angket. Berdasarkan hasil penelitian yang diperoleh dapat disimpulkan bahwa penggunaan buku digital kurikulum darurat mata pelajaran akidah akhlak tergolong baik, terbukti dari hasil anget yang disebar menunjukkan banyaknya responden menjawab “Ya” terhadap beberapa pertanyaan dan nilai hasil ulangan yang mencapai diatas minimum.